Kremlin target U.S.A. : conquest by propaganda - Dunham, Donald (Donald Carl), 1908-2000 (New York : I. Washburn, 1961)
"Explores the form of Kremlin propaganda, and describes the USSR attacks on the United States power position in the world, which culminated in the conquest of Cuba"--Cover.
Part I. The critical challenge. The scope of Kremlin propaganda ; Kremlin propaganda defined ; Conquest by propaganda -- Part II. Target: U.S.A. Combat by slander ; Subversion by delusion ; Defense by control -- Part III. More difficult than war. United States media : the unwitting carriers ; Problems for the American propagandists ; Needed : a political blueprint ; Prescription for the interested citizen ; Prescription for the American propagandists -- Appendixes. Glossary of Kremlin communist upside-down language ; Kremlin propaganda strategems ; Examples of contradictions in Kremlin Propaganda ; "Peaceful Coexistence" by Lenin, Stalin, and Khrushchev ; Carrot and stick statements from the Kremlin ; News and propaganda distribution ; Exchanges U.S.A.-U.S.S.R. Bloc ; Kremlin "Fronts"
Includes bibliographical references and index.
Print reproduction.
Keywords: Propaganda, Russian; Propaganda, Anti-American.; United States -- Foreign public opinion